2020
DOI: 10.1109/access.2020.2978513
|View full text |Cite
|
Sign up to set email alerts
|

PB-NILM: Pinball Guided Deep Non-Intrusive Load Monitoring

Abstract: The work in this paper proposes the application of the pinball quantile loss function to guide a deep neural network for Non-Intrusive Load Monitoring. The proposed architecture leverages concepts such as Convolution Neural Networks and Recurrent Neural Networks. For evaluation purposes, this paper also presents a set of complementary performance metrics for energy estimation. Finally, this paper also reports on the results of a comprehensive benchmark between the proposed network and three alternative deep ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…The vast majority of works employ either the mean absolute error (MAE) or the mean squared error (MSE) in case of power disaggregation and the cross entropy loss for on/off classification. Recent works also investigate alternative loss functions: Quantile regression [123] was employed by [124,125].…”
Section: Training and Loss Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of works employ either the mean absolute error (MAE) or the mean squared error (MSE) in case of power disaggregation and the cross entropy loss for on/off classification. Recent works also investigate alternative loss functions: Quantile regression [123] was employed by [124,125].…”
Section: Training and Loss Functionsmentioning
confidence: 99%
“…The authors of [124] found that their proposed loss increased the performance of two state-of-the-art models compared to the MSE loss. Some works [59,71,76,126] employ GAN loss functions -called 'adversarial loss' in [76] -that classify if the output of the regression DNN is a real or fake appliance load curve.…”
Section: Training and Loss Functionsmentioning
confidence: 99%
“…These algorithms typically outperform unsupervised approaches in terms of accuracy, but require labelled data for training, which can be difficult or expensive to obtain. Numerous supervised learning algorithms have been applied for NILM, including support vector machines (SVMs) [38], [39], and both shallow [40], [41] and deep neural networks (NNs) [42], [43]. Researchers have also used pre-filtering techniques to generate input features for NNs across vastly different time-scales [37] and combined NN-based load identification with unsupervised learning optimization techniques to improve results [44].…”
Section: Nonintrusive Load Monitoring Reviewmentioning
confidence: 99%
“…NILM provides households with cost-effective monitoring of appliance-specific energy consumption, and it can be easily integrated into existing buildings without causing any inconvenience to inhabitants. Several machine learning techniques have been proposed to address the energy-disaggregation [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%